Role of parents relates to vegetable and fruit comsumption on students at Junior High School Hang Tuah 2 Jakarta - Sinta Hikmatun Nisa (ARGIPA (Arsip Gizi dan Pangan), 2020)
Consumption of vegetables and fruit in junior high school students in South Jakarta is very low. Various factors affect the consumption of vegetables and fruits including knowledge of nutrition, the role of parents, peers, and exposure to mass media. This study’s purpose was to determine the relationship of nutritional knowledge, the role of parents, peers, and exposure to mass media with the consumption of vegetables and fruit in Hang Tuah 2 Middle School students. The subjects in this study were students in classes VII and VIII, totaling 130 samples, taken by simple random sampling technique. This study used a cross-sectional design conducted in February-August 2019. Data of knowledge, role of parents, peers, and mass media exposure were taken by interview using a structured questionnaire. Data on vegetable and fruit consumption was taken with Semi-Quantitative Food Frequency. Data analysis using Chi-Square Test. This study showed that 88.5% of students consume less fruits and vegetables. There was a significant relationship between the role of parents with fruit and vegetable consumption (p=0,007), while nutritional knowledge, the role of peers, and exposure to mass media did not have a significant relationship with fruit and vegetable consumption. Keywords: Fruits and Vegetables, Media Exposure, Nutrition Knowledge, Role of Friends, Role of Parents